2012
DOI: 10.1634/theoncologist.2012-0123
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Food and Drug Administration Approval: Peginterferon-alfa-2b for the Adjuvant Treatment of Patients with Melanoma

Abstract: After completing this course, the reader will be able to:1. Describe the setting in which the use of peginterferon-alfa-2b is appropriate for melanoma patients.2. Define the expectations with regard to survival and side effect profile in patients with melanoma receiving peginterferon-alfa-2b.This article is available for continuing medical education credit at CME.TheOncologist.com. The relapse-free survival (RFS) interval, the primary efficacy endpoint, was significantly longer in PEG-IFNtreated patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…[13,14] Recently, pegylated IFN α-2b was approved for use in adult patients with high-risk melanoma based on the results of the European Organisation for Research and Treatment of Cancer (EORTC) 18991 trial in which significant improvement in disease-free survival (DFS) was observed in patients with resected stage III melanoma. [15] The adverse events in adults appear to be similar to nonpegylated IFN α-2b. [16,17] Based on the potential benefit observed with pegylated IFN α-2b in adult patients with melanoma and the more convenient once weekly dosing, we conducted a study to determine the feasibility and safety of pegylated IFN α-2b once weekly as a subcutaneous injection following an initial induction phase of highdose IFN α-2b in children and adolescents with resected 2002 American Joint Committee on Cancer (AJCC) [18] Stage IIC, IIIA, or IIIB cutaneous melanoma.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[13,14] Recently, pegylated IFN α-2b was approved for use in adult patients with high-risk melanoma based on the results of the European Organisation for Research and Treatment of Cancer (EORTC) 18991 trial in which significant improvement in disease-free survival (DFS) was observed in patients with resected stage III melanoma. [15] The adverse events in adults appear to be similar to nonpegylated IFN α-2b. [16,17] Based on the potential benefit observed with pegylated IFN α-2b in adult patients with melanoma and the more convenient once weekly dosing, we conducted a study to determine the feasibility and safety of pegylated IFN α-2b once weekly as a subcutaneous injection following an initial induction phase of highdose IFN α-2b in children and adolescents with resected 2002 American Joint Committee on Cancer (AJCC) [18] Stage IIC, IIIA, or IIIB cutaneous melanoma.…”
Section: Introductionmentioning
confidence: 94%
“…Preclinical and clinical studies indicate that the biological activity of IFN α‐2b is similar, if not better than conventional IFN . Recently, pegylated IFN α‐2b was approved for use in adult patients with high‐risk melanoma based on the results of the European Organisation for Research and Treatment of Cancer (EORTC) 18991 trial in which significant improvement in disease‐free survival (DFS) was observed in patients with resected stage III melanoma . The adverse events in adults appear to be similar to nonpegylated IFN α‐2b …”
Section: Introductionmentioning
confidence: 99%
“…Based on this study result, IFN‐α‐2b has been utilized as a global standard for adjuvant therapy in patients with high‐risk malignant melanoma . Recently, pegylated (PEG) IFN‐α‐2b became available in several countries including the USA and made treatments easier …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recently, pegylated (PEG) IFN-a-2b became available in several countries including the USA and made treatments easier. 5 Pegylated IFN-a-2b in patients with stage III malignant melanoma who have undergone surgery demonstrated statistically meaningful extension of recurrence-free survival (RFS) in a large phase III (European Organization for Research and Treatment of Cancer [EORTC] 18991) study when administrated at 6 lg/kg per week (8 weeks) in the induction phase and 3 lg/ kg per week (up to 5 years in total) in the maintenance phase. 6 ECOG 1684 and EORTC 18991 were randomized, multinational, comparative studies with confirmed efficacies; however, in Japan, both IFN-a-2b and PEG IFN-a-2b remained unapproved for adjuvant treatment of malignant melanoma after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, early clinical studies in vascular tumors, such as infantile hemangioma, giant cell tumor of the mandible, and renal carcinoma, support the selection and monitoring of IFN therapy in relation to elevated plasma or urine FGF concentrations (1214). Recently, a longer-acting formulation of interferon, peginterferon α-2b (Peg-IFN), was approved by the U.S. Food and Drug Administration for the adjuvant treatment of patients with melanoma at a dose of 6 μg/kg (induction for 8 weeks), then 3 μg/kg (maintenance up to 5 years) injected subcutaneously once a week based on a phase III trial (15, 16). …”
Section: Introductionmentioning
confidence: 99%